Students’ Competency Development in Writing Fiction through Mind Mapping Techniques - Abdul Wahid; Sudjoko Sudjoko (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2023)
This study aims to improve Students’ writing competence on fiction to the 4th grade students in Elementary School. This research conducted in the Cijantung 03 Pagi of public elementary school. The teaching learning process was conducted in 2 cycles. On the pre-research, students’ competence on fiction was still low. It yelled 55% of students or 20 of 32 students had lower score (below the minimum completeness criteria/Kriteria Ketuntasan Minimum), after teaching learning process on the first cycle, students ‘writing skill on fiction increased till 75%, then in the 2nd cycle increased to 95%. It can be concluded that using mind mapping technic can increased students’ writing competence on fiction.